2019
DOI: 10.1093/aob/mcy225
|View full text |Cite
|
Sign up to set email alerts
|

Increased water use efficiency and water productivity of arabidopsis by abscisic acid receptors from Populus canescens

Abstract: Background and Aims Water deficit is the single most important factor limiting plant productivity in the field. Poplar is a crop used for second-generation bioenergy production that can be cultivated on marginal land without competing for land use in food production. Poplar has a high demand for water, which makes improving its water use efficiency (WUE) an attractive goal. Recently, we showed that enhanced expression of specific receptors of arabidopsis for the phytohormone abscisic acid (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Previous work indicated that the long-term elevation of ABA accumulation in sp12 induced a 27% increase in whole-plant WUE compared with the wild type (Thompson, Andrews, et al, 2007), without any effect on total fruit production (Smeeton, 2010). Other recent manipulations of ABA content in Arabidopsis and wheat also managed to generate plants growing at both high WUE and high growth rates (Papacek et al, 2019;Yang et al, 2016;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work indicated that the long-term elevation of ABA accumulation in sp12 induced a 27% increase in whole-plant WUE compared with the wild type (Thompson, Andrews, et al, 2007), without any effect on total fruit production (Smeeton, 2010). Other recent manipulations of ABA content in Arabidopsis and wheat also managed to generate plants growing at both high WUE and high growth rates (Papacek et al, 2019;Yang et al, 2016;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the rate-limiting enzyme in ABA biosynthesis, 9-cis-epoxycarotenoid dioxygenase (NCED), led to increased ABA accumulation (Thompson et al, 2000), lower stomatal conductance, and up to 79% higher gravimetric transpiration efficiency (another term for WUE) with only small effects on photosynthetic carbon assimilation or growth (Thompson, Andrews, et al, 2007). Similarly, in Arabidopsis and wheat, activation of ABA signalling through manipulation of ABA receptors led to an increase in WUE of up to 40% without impacting growth significantly (Mega et al, 2019;Papacek, Christmann, & Grill, 2019;Yang et al, 2016). The use of candidate genes therefore holds huge promise for the production of crops with enhanced WUE.…”
mentioning
confidence: 99%
“…Genetic analysis studies revealed quantitative trait loci (QTL) associated with Δ 13 C in different crops including wheat, barley, rice, cotton, soybean, sunflower, tomato, and in a model plant, Arabidopsis (Dhanapal et al., 2015; Hall et al., 2005; Hausmann et al., 2005; Juenger et al., 2005; Lazaa, Kondo, Idetaa, Barlaanb, & Imbea, 2006; Martin, Nienhuis, King, & Schaefer, 1989; Masle, Gilmore, & Farquhar, 2005; Rebetzke, Condon, Farquhar, Appels, & Richards, 2008; Saranga et al., 2001; TalamÉ et al., 2004; Thumma et al., 2001; Wu, Chang, & Jing, 2011). Studies in model plants have identified candidate genes such as MPK12, FRIGIDA, ERECTA as well as receptors for the abscisic acid (ABA) response to be involved in WUE (Des Marais et al., 2014; Karaba et al., 2007; Kuromori et al., 2016; Kuromori et al., 2010; Kuromori, Sugimoto, & Shinozaki, 2011; Lovell et al., 2013; Masle et al., 2005; Papacek, Christmann, & Grill, 2019; Zhang et al., 2016; Zhao, Hu, Li, Yao, & Liu, 2016; Zhao, Chan, et al., 2016). The knowledge of such pathways and their manipulation even in closely related major agricultural crops such as canola and Indian mustard is rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, saccharification potential increased under moderate drought (Wildhagen et al, 2018). At the same time, Papcek et al (2019) have overexpressed poplar ABA receptors in Arabidopsis and observed a 26 % increase in WUE. This suggests that ABA-induced stomatal closure may be an important drought tolerance mechanism in Populus, a result supported by the findings of Brunetti et al 2019, who demonstrated a tight link between ABA-related gene expression and altered photosynthesis and stomatal conductance in response to drought in this bioenergy tree.…”
Section: Developing An Ideotype For Drought Tolerance: Understanding mentioning
confidence: 94%